2004
DOI: 10.1097/00043426-200411000-00011
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of the Neonatal Manifestations of Congenital Dyserythropoietic Anemia Type I

Abstract: Congenital dyserythropoietic anemia (CDA) type I is an inherited disorder characterized by macrocytic anemia with pathognomonic morphologic ultrastructural features of the erythroid precursors. The authors recently cloned the CDAN1 gene and identified one founder missense mutation in all of their Bedouin patients. In a previous study, the authors found that the majority of their 31 Bedouin patients had anemia and jaundice during the first month of life and required blood transfusions; some had persistent pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…Similar observations have been made by others, 29,30 and 17 of 31 patients of Bedouin tribe members were symptomatic in the newborn period. 8 On the other hand, one patient (UPN 409/04) showed macrocytosis without anemia, whereas his sister had moderately low hemoglobin values between 100 and 120 g/L (10-12 g/dL) documented for 30 years. Only 3 cases with borderline anemia were described previously.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similar observations have been made by others, 29,30 and 17 of 31 patients of Bedouin tribe members were symptomatic in the newborn period. 8 On the other hand, one patient (UPN 409/04) showed macrocytosis without anemia, whereas his sister had moderately low hemoglobin values between 100 and 120 g/L (10-12 g/dL) documented for 30 years. Only 3 cases with borderline anemia were described previously.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 Seventyseven cases from 68 families have been published as case reports, including 9 of 21 confirmed cases of CDA I collated in the German CDA registry. In addition, there are 70 more cases in the large Bedouin tribe described by Tamary et al 6,7 and Shalev et al 8 from Israel in 1996. CDA I is characterized by congenital anemia, ineffective erythropoiesis, and characteristic morphologic abnormalities on both light and electron microscopy.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most CDA patients have only mild or moderate anemia and do not require medical intervention. About 50% and 10% of neonates with CDA I 45 and CDA II, 46 respectively, need at least one erythrocyte transfusion, and some remain transfusion-dependent in the following years. In most adolescents and adults, the need for transfusions is limited to aplastic crises, pregnancy, severe infections or major operations.…”
Section: Complications and Therapeutic Approachesmentioning
confidence: 99%
“…The identification of genes responsible for type I and type II of congenital dyserythropoietic anemia (CDA)(7) has allowed confirmation of their diagnoses in addition to electron microscopic examination of the erythroblasts in the bone marrow (8,9). Research into hereditary stomatocytoses (Figure 1b) has revealed the involvement of very different transmembrane proteins localized to the lipid bilayer (10)(11)(12), and the molecular basis of monovalent cation transport in this group of rare red cell disorders (13,14).…”
Section: Introductionmentioning
confidence: 99%